The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.str.2017.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Substrate Recognition by the Ankyrin Repeat Domain of Human DHHC17 Palmitoyltransferase

Abstract: Summary DHHC enzymes catalyze palmitoylation, a major post-translational modification that regulates a number of key cellular processes. There are up to 24 DHHCs in mammals and hundreds of substrate proteins that get palmitoylated. However, how DHHC enzymes engage with their substrates is still poorly understood. There is currently no structural information about the interaction between any DHHC enzyme and protein substrates. In this study we have investigated the structural and thermodynamic bases of interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
64
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 47 publications
(59 reference statements)
1
64
1
Order By: Relevance
“…The acyl group is added by a family of protein acyl transferases (PATs) that are characterised by a DHHC motif within their catalytic domain. The structure of a human PAT, DHHC17, has recently been solved 4 , but despite this and the identification of a large number of S-acylation sites, there are no recognisable motifs around the modified cysteines of the substrate proteins. A recent study that monitored S-acylation directly using mass spectrometry (MS) suggested that cysteines were modified independently of any sequence motif around the site, in a stochastic process that depends upon the accessibility of any given cysteine to the action of a PAT 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The acyl group is added by a family of protein acyl transferases (PATs) that are characterised by a DHHC motif within their catalytic domain. The structure of a human PAT, DHHC17, has recently been solved 4 , but despite this and the identification of a large number of S-acylation sites, there are no recognisable motifs around the modified cysteines of the substrate proteins. A recent study that monitored S-acylation directly using mass spectrometry (MS) suggested that cysteines were modified independently of any sequence motif around the site, in a stochastic process that depends upon the accessibility of any given cysteine to the action of a PAT 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The affinity of the zDABM of SNAP25 for the ANK domain of zDHHC17 was calculated to be ~ 11 M, although full-length SNAP25 had a higher affinity [19]. This interaction affinity is clearly sufficient to allow robust isolation of the protein complex by co-IP.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work identified a consensus recognition short linear motif (SLiM) in these and other substrates that mediate binding to the ANK domain of both zDHHC17 and zDHHC13 [18]. The 6-amino acid [VIAP][VIT]XXQP consensus motif makes key contacts with asparagine-100 and tryptophan-130 of zDHHC17 [19]. We named the consensus SLiM the "zDHHC Ankyrin repeat Binding Motif (zDABM)" [20].…”
mentioning
confidence: 99%
See 2 more Smart Citations